Non‐centrosomal microtubules regulate F‐actin organization through the suppression of GEF‐H1 activity. (22nd February 2013) - Nagae, Shigenori; Meng, Wenxiang; Takeichi, Masatoshi
<x xml:space="preserve">Abstract</x> Animal cells contain two populations of microtubules: one radiating from the centrosome and the other growing from non‐centrosomal sites. Whether or not they have differing roles in cellular architecture and function remains not fully understood. The cytoplasmic protein Nezha (also known as CAMSAP3) stabilizes non‐centrosomal microtubules by attaching to their minus ends. Here, we found that depletion of CAMSAP3 in HeLa cells resulted in a relative increase in centrosomal microtubules, and this change was accompanied by accelerated actin stress fiber formation. In these cells, RhoA activity was upregulated, and the soluble fraction of GEF‐H1, a RhoGEF whose activity is inhibited by binding to microtubules, increased, explaining why stress fiber formation was promoted. We further found that CAMSAP3 depletion led to an increase in detyrosinated microtubules, and these microtubules did not interact with GEF‐H1. These findings suggest that CAMSAP3‐anchored non‐centrosomal microtubules capture GEF‐H1 more efficiently than other microtubules do and that a balance between these microtubules is important to maintain proper actin organization.